Desain dan Karakterisasi Kinerja Electric Submersible Pump (ESP) Khusus Sumur Kandungan Gas Liquid Ratio (GLR) Tinggi: Analisis Ekonomi dan Kelayakan Investasi - Mohd Wirawan Putra Pamungkas (Lembaran publikasi minyak dan gas bumi, 2025)
The decline in oil well production is caused by natural factors such as reservoir pressure decline, increased water content, and high gas-liquid ratio (GLR), which also affect artificial lift performance. Electric Submersible Pump (ESP) is chosen as a solution, despite challenges such as gas lock and uneven wear in high GLR directional wells. ESP planning focused on component design, such as motor protectors and the use of Single Feature Rotary Gas Separators to address gas issues. The implementation of ESP in three wells showed a significant increase in production: Well AZ-049 increased by 12.7% (from 902 BFPD to 1017 BFPD), Well AZ-084 increased by 86%, and Well AZ-025 achieved the highest increase of 124% (from 246 BFPD to 551 BFPD). Collectively, this project generated a total gross production of 2817 BFPD and a net oil gain of 364.5 BOPD. Economic analysis shows excellent financial viability with a Net Present Value (NPV) of $3.089 million, a Profitability Index (PI) of 30.07, and a Rate of Return (ROR) of 2761.33%. Liquidity risk is very low, indicated by a Pay Out Time (POT) of only 0.035 years (approximately 13 days). These results indicate that the ESP project is a highly potential investment.